Enhancing Galactomannan Recovery from Coconut Meat: Impact of Autoclaving Pretreatment in a High-Shear Compartment Reactor System - Arief Rakhman Affandi; Sinta Dewi; Iffah Muflihati; Rini Umiyati (Biology, Medicine, & Natural Product Chemistry, 2026)
Galactomannan in coconut meat is tightly bound within its fiber matrix, limiting extraction efficiency. Autoclave pretreatment, combining heat, pressure, and moisture, can loosen this structure and improve galactomannan release. This study examined the effects of autoclaving temperature (100°C–130°C) and water addition (0–45%) on the physical and chemical properties of grated coconut prior to extraction. This study examined the effect of autoclaving temperature on the physicochemical properties and extraction yield of galactomannan. Four pretreatment temperatures were evaluated: 100, 110, 120, and 130 °C. The 100°C treatment produced the highest yield (8.45%), swelling power (8.67%), color values (L* = 53.44, a* = 5.48, b* = 9.09), and reducing sugar content (18.03%). Statistical analysis confirmed that autoclaving temperature significantly influenced extraction yield. Overall, 100°C was identified as the optimal pretreatment condition for enhancing galactomannan extraction from coconut meat.